MANAJEMEN DISTRIBUSI DAGING QURBAN MASJID AT TAQWA DESA BATUR KABUPATEN BANJARNEGARA - Muhammad Naufal Hasibuan; Hari Santoso Wibowo; Fathurrahman Masrukan (Institut Agama Islam Negeri Parepare, 2026)
This research highlights the logistical vulnerability caused by an annual 25-ton surplus of sacrificial meat in Batur Village, Banjarnegara. This study aims to analyze the meat distribution management utilizing the POAC framework. The method employed is a descriptive qualitative case study with Miles and Huberman analysis techniques. The results indicate that integrating a 23-musala-based data system, innovative grid-tarpaulin estimation packaging, and regional clustering effectively resolves meat accumulation tactically. The implication of this study emphasizes that social-capital-based logistics management engineering is highly effective in overcoming livestock food distribution gaps in surplus areas